PENINGKATAN HASIL BELAJAR IPS SISWA DENGAN MENGGUNAKAN METODE LATIHAN DI KELAS IV SD NEGERI 006 TRI MULYA JAYA KECAMATAN UKUI - Ngadimin ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
This research is a classroom action research is motivated by the low learning outcomes IPS fourth grade students SD Negeri 006 Tri Mulya Jaya Kecamatan Ukui. This study was conducted by two cycles by applying the method of exercise. The data used in this study is the teacher and student activity data and the results of social studies students. The study states that the activities of teachers and students and learning outcomes IPS has increased after the action, this is evidenced by: (a) the activities of teachers has increased, in the first cycle of activity for teachers to get a score of 19 (63.00%) with a category (quite perfect ). In the second cycle increased with the acquisition of a score of 22 (73.00%) with a category (perfect); (B) the activity of students also increased, in the first cycle of activity students obtain a score of 47 (60.00%) in the category "High". While on the second cycle increased student activity with a score of 52 (67.00%) to the category of "high"; and (c) the results of social studies has increased, students are worth being the same as the KKM (interval 65-74) are in the first cycle there are 7 people (54.00%) and the second cycle increased by 8 votes (62.00%). To score high value (interval 75-84) in the first cycle there were 3 people (23.00%) and the second cycle there are also 3 people (23.00%). Students who reach KKM in the first cycle there are 10 people (77.00%) and the second cycle there are 11 people (85.00%).